'My Fast is Better Than Your Fast': Concealing Interreligious Evaluations and Discerning Respectful Others in Gondar, Ethiopia. Issue 3 (27th May 2022) - Dulin, John
ABSTRACT: This essay argues that modalities of interreligious conflict and coexistence in Gondar, Ethiopia entail shifting sites of discernibility and concealment. In religiously mixed interactions, both parties tend to see concealment as a key facet of a self-conscious ethical project of harmonious, interreligious relations. Hence, many reserve interreligious evaluations for homogenous settings of religious insiders, where the expressions cannot frame real-time mixed interactions in antagonistic terms. On occasion, though, the concealment is unsustainable, and interreligious evaluations leak into shared spaces, becoming discernible in a mutually recognisable way, thus creating open conflict. Adhering to norms of concealment marks one as a respectful other, however, these norms can conflict with religious ethical imperatives. The way they conflict differs for Orthodox Christians, Muslims, and Pentecostals. Moreover, the significance attributed to concealment/revelation within religious and interreligious value frameworks often shapes patterns of relations across religious boundaries, including routine mutuality, ambivalence, and escalating tensions.